2009
DOI: 10.1016/j.yfrne.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Protective actions of sex steroid hormones in Alzheimer’s disease

Abstract: Risk for Alzheimer’s disease (AD) is associated with age-related loss of sex steroid hormones in both women and men. In postmenopausal women, the precipitous depletion of estrogens and progestogens is hypothesized to increase susceptibility to AD pathogenesis, a concept largely supported by epidemiological evidence but refuted by some clinical findings. Experimental evidence suggests that estrogens have numerous neuroprotective actions relevant to prevention of AD, in particular promotion of neuron viability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
366
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(379 citation statements)
references
References 405 publications
(492 reference statements)
12
366
1
Order By: Relevance
“…32,33 In addition, testosterone showed to have a neuroprotective role in animal studies, 34,35 and some studies have shown protective actions of sex hormones in several neurodegenerative diseases. 36 Regarding the HSD17B1 gene, although we did not found an effect in AO variation, this does not exclude other variants in other estradiollinked genes as possible modifier candidate genes in FAP ATTRV30M.…”
Section: Ar Gene and Ao Variabilitycontrasting
confidence: 63%
“…32,33 In addition, testosterone showed to have a neuroprotective role in animal studies, 34,35 and some studies have shown protective actions of sex hormones in several neurodegenerative diseases. 36 Regarding the HSD17B1 gene, although we did not found an effect in AO variation, this does not exclude other variants in other estradiollinked genes as possible modifier candidate genes in FAP ATTRV30M.…”
Section: Ar Gene and Ao Variabilitycontrasting
confidence: 63%
“…Androgens may regulate the production and the levels of Aβ, by a classic genomic mechanism and rapid non-genomic signaling or via aromatization to estradiol and activation of estrogen pathways [81,82]. Testosterone can attenuate the toxicity of Aβ in cultured hippocampal neurons via a rapid, estrogen-independent mechanism [83].…”
Section: Effects Of Androgensmentioning
confidence: 99%
“…However, these subsequent dysfunctions are characteristic of aging effects due to loss of hormones and its effect on mitochondria in both women and men, which has been widely documented in the literature [30]- [36]. This is why we focus on the effects produced by steroid hormones due to their ability to control and regulate gene protein products.…”
Section: The τ Hyperphosphorylation and β-Amyloid Plaquesmentioning
confidence: 99%
“…As discussed in Pike et al [30], estrogen's neuro-protective actions are modulated by progesterone [51] [52], whereas static progesterone exposure always inhibits estrogen's actions, synthetic or otherwise. However, the cyclic delivery of P4 and E2 will allow for the increase of E2 receptors [48] [49].…”
Section: The τ Hyperphosphorylation and β-Amyloid Plaquesmentioning
confidence: 99%